Tolerance and Pluralism in the Philosophical Writings of Rabbi Joseph B. Soloveitchik - Hyatt, David (Revista Ciências da Religião - História e Sociedade, 2014)
While much has been written about the dynamics of inter and intra-religious dialogue in the philosophical writings of R. Soloveitchik, this discussion has not been put before the lens of the philosophy of tolerance and pluralism.[i] After a brief review of some of the conceptual problems underlying these terms, I apply them to R. Soloveitchik's writings. First I explore his attitude toward the group whom he found it most difficult to tolerate--secular Jews and non-Jews. I then introduce the notion of incommensurability while examining his relation to people's of other faiths, an arena where doors are opened to both tolerance and pluralism. Next, I explore his conception of cognitive pluralism as it is presented in The Halakhic Mind, marking both the limitations and the possibilities of pluralism in light of phenomenological theories of intuition and intention. I then elicit Gadamer's notion of prejudice, showing how it resolves some of the tensions inherent in adopting a tolerant or pluralistic stance. Finally I examine the consequences of R. Soloveitchik's dialectical methodology, claiming that R. Soloveitchik's use of an "unsolvable" dialectic necessitates a pluralistic approach to ethics and ideas. Finally, I also question whether R. Soloveitchik can indeed maintain his desired dialectic schism. Here I show how one side of the dialectic—that represented by such terms as Adam II, "humility", "gvura [strength]" or revelational consciousness—has a supplementary effect, that of destabilizing the dialectical schism through a process variously described as a recoil, withdrawal, retreat, catharsis, self-contraction or tzimtzum. This process parallels the disposition necessary to engage in toleration. [i] See Finkelman, Yoel. “Religion and Public Life in the Thought of Rabbi Joseph Soloveitchik,” Jewish Political Studies Review 13:3-4 (Fall 2001), 41-70. Hartman, David. Love and Terror in the God Encounter: The Theological Legacy of Rabbi Joseph B. Soloveitchik, Volume 1. (Vermont: Jewish Lights Publishing, 2001). Meir, Ephraim. "David Hartman on the Attitudes of Soloveitchik and Heschel towards Chistianity" in Modern Judaism, 23,1 (2003), 12-31. Rynhold, Daniel. “The Philosophical Foundations of Soloveitchik’s Critique of Interfaith Dialogue.” Harvard Theological Review 96, 1 (2003) 101-120. Sagi, Avi. Tradition vs. Traditionalism, trans. Batya Stein. (Amsterdam: Rodopi, 2008).